A Branch-to-Branch Through-and-Through Wire Technique to Redirect a Branch Malposition in Multibranched Endovascular Aortic Aneurysm Repair. (October 2021) - Youssef, Marwan; Gunaseelan, Meera
Objective: To describe a novel technique to redirect a malrotated branch when treating a symptomatic juxtarenal aortic aneurysm using an off-the-shelf multibranched endograft. Technique: A 75-year-old patient was admitted because of a symptomatic juxtarenal aortic aneurysm with a maximum diameter of 9.2 cm. The aneurysm showed no infrarenal neck. Because of his comorbidities, an endovascular repair using off-the-shelf multibranched endograft was considered as urgent procedure. During the deployment, the devise malrotated clockwise. The incorporation of the renal branches was performed successfully; however, the superior mesenteric artery (SMA) branch was malpositioned, so that the SMA could not be cannulated. Both celiac and SMA branches were simultaneously cannulated and snared outside of the endograft redirecting the malrotated SMA branch (a branch-to-branch through-and-through wire technique). Leaving the through-and-through wire in situ, the SMA could be intubated using parallel wire through the SMA branch. The final angiogram showed a good perfusion of the renovisceral vessels. The aneurysm was completely excluded. The patient was discharged into a rehabilitation facility 8 days later without complications. The 12-month follow-up period was uneventful. Conclusion: A branch-to-branch through-and-through wire technique for branch repositioning is feasible and may present a bailout tool.